Komunitas Ikan Karang di Pulau Ternate dan Sekitarnya - Rizkie Satriya Utama; Isa Nagib Edrus; Petrus Christianus Makatipu (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Reef Fish Community in the Adjacent Waters of Ternate Island. Considering that the development of coastal region in the North of Moluccas may affect the population of reef fishes, a research on coral reef community structure is performed using underwater visual cencus on a permanent belt transect. The selected indicator monitoring used were eight families of reef fishes. A total of 108 species of reef fishes were identified, consisted of 31 species of corallivorous, 45 species of herbivorous fishes and 32 species carnivorous fishes (based on punctuation group). Density means of a corallivorous group is 1.598 ± 283 individual/ha, a herbivorous group is 4.751 ± 1.034 individual/ha, and a carnivorous group is 890 ± 622 ekor/ha. The average of reef fish stocks is 420 ± 162 kg/ha that consist of 320 ± 130 kg/ha for herbivorous fishes and 100 ± 64 kg/ha for carnivorous fishes. Indicator fish dominance were attained by Chaetodon baronessa, C. kleinii, C. lunulatus, C. melannotus, C. octofasciatus, C. trifascialis, and Heniochus varius. Herbivorous fishes (84%) more dominat than carnivorous (16%) in terms of individual composition. Dominant species of herbivorous fishes included Acanthurus pyroferus, Chlorurus bleekeri, C. Sordidus, Ctenochaetus binotatus, C. striatus, Scarus dimidiatus, S. ghobban, Siganus vulpinus, and Zebrasoma scopas. The one of carnivorous fishes dominated was only Lutjanus biguttatus. Increasing trend of species numbers and density for corallivorous, herbivorous and carnivorous fishes occured from 2015 until 2017 in majority of study sites. In contrast, the biomass values not increased in majority of the sampling sites.